Gesundheit als Ware? Managed Care, GATS und die "Amerikanisierung" des deutschen Gesundheitssystems - Mosebach, Kai (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2003)
The globalization process and national reform policies provoke concerns about the future of the German health care system. The anti-globalist movements are fearing a kind of 'Americanization' of the Bismarckian-style German model. The article shows that such concerns are exaggerated at the moment but nevertheless point correctly to the already started process of the economization of health care delivery on a global level. Although concepts of managed care and integrated delivery systems have begun to be implemented in Germany the institutional context is rather different from the US. But the neo-liberal context of the Single European Market and the General Agreement on Trade in Services (GATS) could pose a threat to the institutional body of the solidarity based health care system in Germany. The politics of fiscal austerity, lowering ancillary wage costs through privatization and competitiondriven reform policies might alter the shape of the German model in future, resembling more the US-model than its Bismarckian-style inheritance.